Unsur Metafiksi yang Ditemukan Dalam Film Inside Out (2015): Analisis Psikoanalitik - Putri Ratta, Rizka Auliya Aruvi (Universitas Harapan Medan, 2024)
This research is aimed to analyze the metafictional elements found in Inside Out (2015) film. The researcher analyzed the metafictional elements contained in Joy’s V.O lines in Inside Out (2015) film based on Waugh’s (1984) analysis of metafiction and the psychoanalysis of Joy’s emotional development in Inside Out (2015) film. The psychoanalysis of Joy is done by applying Freud’s (1923) theory of The Structure of Personality; the id, ego, and superego. The sources were taken from various e-books, journals, scientific articles, and other library resources to support this research. The result of this research concluded as follows; 1) the twenty-one data found in the film collectively contained metafiction; and 2) the id, ego, and superego are successfully applied to the analysis of Joy’s emotional development.